2014
DOI: 10.4049/jimmunol.1303211
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: NKG2ChiCD57+ NK Cells Respond Specifically to Acute Infection with Cytomegalovirus and Not Epstein–Barr Virus

Abstract: Cytomegalovirus (CMV) induces the expansion of a unique subset of human NK cells expressing high levels of the activating CD94-NKG2C receptor that persist after control of the infection. We investigated whether this subset is indeed CMV-specific or is also responsive to acute infection with Epstein-Barr virus (EBV). Here we describe a longitudinal study of CMV-seronegative and -seropositive students who were acutely infected with EBV. The NKG2Chi NK subset was not expanded by EBV infection. However, EBV infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
132
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(143 citation statements)
references
References 27 publications
6
132
5
Order By: Relevance
“…It is possible that infection with certain viruses leads to subclinical reactivation of CMV, although no overt CMV viremia could be detected in the studies of HBV and HCV infection and in hantavirus infection (Béziat et al 2012;Björkström et al 2011b). By contrast, in a study of college students experiencing acute infectious mononucleosis caused by Epstein-Barr virus infection, we did not detect an expansion of the CD94-NKG2C + NK cell subset in CMV-seropositive individuals (Hendricks et al 2014). Taken together, these findings suggest that infection with CMV is absolutely necessary to generate this population of CMV-specific CD94-NKG2C + NK cells, which respond during reactivation of CMV.…”
Section: Nk Cell Memory Following Human Cytomegalovirus Infectioncontrasting
confidence: 71%
See 1 more Smart Citation
“…It is possible that infection with certain viruses leads to subclinical reactivation of CMV, although no overt CMV viremia could be detected in the studies of HBV and HCV infection and in hantavirus infection (Béziat et al 2012;Björkström et al 2011b). By contrast, in a study of college students experiencing acute infectious mononucleosis caused by Epstein-Barr virus infection, we did not detect an expansion of the CD94-NKG2C + NK cell subset in CMV-seropositive individuals (Hendricks et al 2014). Taken together, these findings suggest that infection with CMV is absolutely necessary to generate this population of CMV-specific CD94-NKG2C + NK cells, which respond during reactivation of CMV.…”
Section: Nk Cell Memory Following Human Cytomegalovirus Infectioncontrasting
confidence: 71%
“…Of note, in a longitudinal study of college students at University of Minnesota with Dr. Kristen Hogquist (Odumade et al 2012), we demonstrated that acute infection with EBV did not expand CD94-NKG2C + NK cells in CMV-seronegative students. Importantly, EBV infection did not drive expansion of the CD94-NKG2C + NK cells present in students previously infected with CMV (Hendricks et al 2014). Coinfection with EBV and CMV did elicit an increased frequency of NKG2A + CD57 + NK cells (that did not express CD94-NKG2C receptors) in the blood of EBV-infected individuals that persisted into latency.…”
Section: Specificity Of Nk Cell Memory In Mice and Humansmentioning
confidence: 89%
“…EBV serostatus, which has been associated with altered NK cell phenotype in HCMV-exposed Europeans, 7 had no significant effect on NK cell subset distribution, other than a minor increase in CD56 dim cell frequency (supplemental Figure 5A-G), supporting a recent paper suggesting that acute EBV coinfection has no major effect on NKG2C 1 CD57 1 NK cells. 30 …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, HCMV and EBV coinfection did not affect NK cell phenotype or function. EBV coinfection has been associated with more extensive NK cell differentiation compared with HCMV alone in some European studies, 7 but not in a recent US study, 30 suggesting that perinatal HCMV infection alone is sufficient to drive NK cell differentiation or that infections other than EBV may also have an effect in this Gambian cohort. Of note, the biphasic kinetic of NK cell differentiation is not accompanied by a similar biphasic differentiation of T-cell populations, which is consistent with the suggestion that HCMV infection independently affects T-cell and NK cell populations.…”
mentioning
confidence: 99%
“…32,33 "Memory-like" NKG2C pos NK cells found in patients receiving bone marrow or peripheral blood stem cell transplants from CMV pos donors displayed more durable IFN-g production compared with NK cells from CMV neg donors. 34 NK cell subset phenotypes and cytotoxic capacity during asymptomatic pediatric EBV infections are not known.…”
Section: Cd16mentioning
confidence: 99%